Noisy Light Augments the Na+ Current in Somatosensory Pyramidal Neurons of Optogenetic Transgenic Mice - Mabil, Pedro; Huidobro, Nayeli; Torres-Ramirez, Oswaldo; Flores-Hernandez, Jorge; Flores, Amira; Gutierrez, Ranier; Manjarrez, Elias (Frontiers in Neuroscience, 2020)
In previous reports, we developed a method to apply Brownian optogenetic noise-photostimulation (BONP, 470 nm) up to 0.67 mW on the barrel cortex of in vivo ChR2 transgenic mice. In such studies, we found that the BONP produces an increase in the evoked field potentials and the neuronal responses of pyramidal neurons induced by somatosensory mechanical stimulation. Here we extended such findings by examining whether the same type of BONP augments the Na+ current amplitude elicited by voltage-clamp ramps of dissociated pyramidal neurons from the somatosensory cortex of ChR2 transgenic and wild type mice. We found that in all neurons from the ChR2 transgenic mice, but none of the wild type mice, the peak amplitude of a TTX-sensitive Na+ current and its inverse of latency exhibited inverted U-like graphs as a function of the BONP level. It means that an intermediate level of BONP increases both the peak amplitude of the Na+ current and its inverse of latency. Our research suggests that the impact of BONP on the Na+ channels of pyramidal neurons could be associated with the observed augmentation-effects in our previous in vivo preparation. Moreover, it provides caution information for the use of an appropriate range of light intensity, <0.67 mW, which could avoid opto non-genetics (also termed “optonongenetic”) related responses due to light-induced temperature changes.